MOTIVASI PELAKU ONLINE HUMAN TRAFFICKING - Zuliana, Rheta; Sujarwo, Sawi (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2018)
This study aims to find out more about the dynamics of psychology and motivation factors of online human trafficking perpetrators on two subjects of early adult men who became prisoners Dirreskrimum Polda South Sumatra. To achieve research objectives researchers used a qualitative approach. The technique was used in 2 men aged 28 and 31 who had been in custody for several months. Based on the results of research known that the motivation of online human trafficking is divided into two, i.e. internal motivation and external motivation. Internal motivation of online human trafficking actors is a form of interest and lifestyle expression, while external motivation of human trafficking is the influence of peers, family demands and economic factors. Other findings from this study are the similarity of educational background, and economic causes. In addition, it was found that the influence of drugs and suicidal desires that arise due to heavy burden of the subject's life. But it does not make them desperate in the pursuit of future dreams and become a reference to be able to improve themselves and become a better perso